Evaluating the Dynamic Psychological and Behavioral Changes of Water‐Saving in Public Buildings Under Effective Interventions - Bowen Duan; Jinliang Gao; Wenyan Wu; Huizhe Cao; Wenjuan Guo; Jinghui Wang; Shanshan Zhang; Chao Wen; Yuan Tian; Chang Shen (Water Resources Research, 2025)
Abstract This paper addresses the critical aspect of water conservation in public buildings within the context of sustainable urban water resources management. While conventional approaches rely on pricing controls and water‐saving appliances, this research emphasizes the key consideration of psychological factors influencing users' willingness to conserve water. Through a survey involving 1,206 volunteers, an expanded theory of planned behavior model is constructed and analyzed to evaluate the impact of water‐saving attitudes, subjective norms, self‐efficacy, and perceived behavioral control on individuals' water‐saving behavior. Intervention experiments conducted in three types of public buildings equipped with smart water meters unveil the nuanced dynamics of real‐time water‐saving behavior and its responsiveness to external interventions. Findings underscore the collective influence of subjective norms, water‐saving attitudes, self‐efficacy, and perceived behavioral control on individuals' intentions and behaviors. Noteworthy is the observed time lag and diminishing impact of external interventions, where economic, feedback, and subjective norms interventions prove more effective. This study not only contributes a theoretical framework but also provides practical insights, emphasizing the need for consistent and targeted external interventions. Practitioners, decision‐makers, and stakeholders are urged to recognize the profound impact of users' psychological factors on public water‐saving behavior and strategically employ interventions for sustained positive outcomes.